Numerical and experimental study of externally reinforced RC slabs using FRPs subjected to close-in blast loads. (October 2021) - Reifarth, C.; Castedo, R.; Santos, A.P.; Chiquito, M.; López, L.M.; Pérez-Caldentey, A.; Martínez-Almajano, S.; Alañon, A.
Highlights: Full-scale blast testing of RC slabs with different scaled distances. Study of the reinforcement effect of CFRP and GFRP on RC slabs. The use of CFRP and GFRP on RC slabs improves their blast resistance. Novel use of LSDYNA's Mat_058 subjected to high strain rates. Abstract: The use of woven Fiber Reinforced Polymer (FRP) as strengthening material on full-scale Reinforced Concrete (RC) slabs was studied in this paper. Carbon (CFRP) and E-glass (GFRP) fibers were tested for comparison. The specimens of the trials were subjected to blast loads at scaled distances of 0.83 m/kg 1/3, 0.42 m/kg 1/3 and 0.21 m/kg 1/3, varying both charge and distance to the slab. Furthermore, Finite Element (FE) numerical models have been developed to study, in-depth, the response of the structural elements. A non-reinforced slab facing the highest scaled distance has been used as calibration test. It was monitored with pressure gauges and accelerometers, obtaining errors of around 2% and 5%, respectively, compared with the models' predictions. Seven other trials were carried out and used as validation tests. The explosive charge model was developed using the *LOAD_BLAST_ENHANCED (LBE) tool available in the LS-DYNA software. Two concrete material models have been tested, CSCM and RHT, achieving better results with the first one. To model the FRP reinforcement, *MAT_058 (LAMINATED_COMPOSITE_FABRIC) was used. Applying CFRP resulted in a generally reduced damage area on both surfaces especially at intermediate scaled distances. Concerning the specimens reinforced with GFRP, further investigation needs to be conducted as the field test outcomes were not entirely conclusive due to the bonding of the fiber on concrete. The experimental results were closely reproduced with the developed numerical models, with errors in terms or surface damage below 15%.